Reconstructing Copyright-Based Fiduciary Security in the Digital Economy: An Indonesian Legal Perspective - Marsella; Rafiqi; Anne Gunawati; Achamd Jaelani; Hambali (Jurnal Wawasan Yuridika, 2025)
Copyright has been recognized as an object of fiduciary security under Law Number 42 of 1999, yet its implementation continues to face structural barriers. This study aims to identify and analyze the normative and administrative problems that hinder the imposition of fiduciary security over copyright, and to formulate regulatory and institutional reconstruction strategies necessary for enabling copyright to function effectively as collateral within the financing system. The research employs a normative legal specification with a descriptive–analytical design, applying both a statute approach and a conceptual approach. Data were collected through document study and literature review, and analyzed qualitatively by interpreting positive legal norms and administrative documents related to copyright-based fiduciary security. The findings reveal three principal obstacles: the absence of valuation standards, the lack of system integration between the Directorate General of Intellectual Property and the Directorate General of General Legal Administration, and the unavailability of technical protocols for intellectual property transactions. The study recommends strengthening valuation standards, integrating registration systems, and formulating implementing regulations as the basis for reconstructing the use of copyright as an object of fiduciary security. This research contributes theoretically by enriching the discourse on guarantees over intangible assets, practically by offering a regulatory and institutional framework for policymakers and financial institutions, and academically by addressing the gap that links legal norms, institutional capacity, and technical procedures in the imposition of copyright-based fiduciary security.